Motivation in the classroom to develop English Speaking skills: Motivación en el aula para desarrollar habilidades de habla en inglés - Navas Colón, William Ricardo (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2023)
This research aims to show the magnitude of importance that motivation can have in the learning process of English. For this reason, various elements thay may alter student´s motivation are mentioned, making use of a questionnaire as an initiation process that were given to students from the second level of English of the Pontifical Catholic University of Ambato. The main factors of the research shows the importance of student´s interests, teachers role, daily habits, along with others. Eventually, some recommendations for improving student´s motivation to develop English speaking skills are proposed for future growth.